PERAN KELUARGA DALAM PEMBENTUKAN NILAI KARAKTER PADA ANAK USIA DINI (Studi Kasus Di Taman Kanak-Kanak Al-Mahri Tahun 2024) (Jurnal Sosial Humaniora dan Pendidikan, 2025)
The purpose of this study was to determine the role of the family in the formation of character values of responsibility in early childhood at Al-Mahri Kindergarten Medan. This type of research is descriptive with a qualitative approach. The subjects in this study were parents of early childhood, educators, and early childhood at Al-Mahri Kindergarten. Al-Mahri Kindergarten is located at Jl. Pertahanan Komp. Villa Permata Indah Block F no. 3, Marindal Dua, Patumbak District, Deli Serdang Regency, North Sumatra. The sample taken was 11 people. Data collection techniques were by interview with a questionnaire and documentation instrument. The results of the study obtained: 1. Based on the results of the study that has been conducted, the family has carried out its role in the formation of character values of responsibility in early childhood at Al-Mahri Kindergarten Medan. 2. The character values of responsibility have grown in early childhood at Al-Mahri Kindergarten Medan. 3. Parents act as role models, givers of direction, and reinforcers of positive values in children. Some character values that are emphasized in the family include honesty, responsibility, politeness, and cooperation. 4. Cooperation between family and school is very important in the formation of character in early childhood. Schools can provide programs that support character formation, while the family plays a role as a reinforcer at home.